The Effect of the Promotional Mix on the Interest of Village Visitors Kampung Patin Riau - Mutiara Salsabila; Ira Dwi Mayangsari (Budapest International Research and Critics University, 2022)
This research was conducted to determine the results of the Effect of Promotional Mix on Visitor Interest in Kampung Patin Riau Tourism Village. This study uses a probability sampling technique, namely simple random sampling. The technique that will be used in this research is simple random sampling, namely the process of taking samples of members of the population at random without regard to the overall level in the population. The exact number of the population in this study cannot be known with certainty because the number varies. So in this study sampling using the formula from Lemesshow, then obtained a sample of 96.4 and rounded up to 100 respondents. In this study, with the results of hypothesis testing with t-test, the results of T-count > T-table (2,936 > 1.985) and a significance of 0.004 < 0.05 then Ho is rejected and Ha is accepted, so it can be stated that there is a significant effect of the promotion mix on interest visitors to the Patin Village Tourism Village. Based on the results of research on